UNDERGRADUATE STUDENT BENEFITS FROM COLLEGIATE RECREATIONAL SPORTS - Yudha, Brio Alfatihah Rama; Subarjah, Herman; Ma’mun, Amung; Berliana, Berliana (ASEAN Journal of Sport for Development and Peace, 2021)
Collegiate recreational sports provide many avenues for student development resulting in various benefits that have been supported through theoretical and empirical research. the purpose of this article is to understand the advantages students benefits from participating in recreational sports in college. This literature study begins by using keywords in five databases containing credible English journals. The results of this study there are five important benefits of collegiate recreational sports activities, including: physiological benefits, academic achievement benefits, self-esteem benefits, social benefits and stress management benefits. Further expected from this study is the research and literature on benefits of collegiate recreational sports participation, collectively articulate the multifaceted impacts of collegiate recreational sports on college and university campuses nationwide. To shift the too frequent perception that student participation in collegiate recreational sports programs is a residual, to recognition of the important benefits of participation in these programs based on the results of this study, collegiate recreational sports programs need to better position, or reposition, themselves.